Capacity Sharing Between Competitors - Guo, Liang; Wu, Xiaole (Management Science, 2018)
Market competition may lead to mismatch between supply and demand. That is, overpricing may give rise to underselling, and underpricing may yield stockout. Capacity sharing is a common practice to align excessive capacity with excessive demand. Yet, the strategic interaction between competition and capacity sharing has not been adequately addressed. In this paper, we investigate optimal strategies and firm profitability of capacity sharing between competing firms under both ex ante and ex post contracting, depending on whether the capacity-sharing price is determined before or after price setting in the buyer market. We show that, with symmetric capacity, committing to an overly high capacity-sharing price may not necessarily improve firm payoffs. Capacity sharing softens price competition under either contracting scheme, whereas the optimal capacity-transfer price and equilibrium profits may be nonmonotonically influenced by buyer loyalty. The equilibrium outcome under ex ante contracting is more sensitive to variations in market parameters than ex post contracting. As a result, ex ante contracting is more likely to be preferred when the endowed capacity is low or buyer loyalty is high. However, when firms’ capacity is asymmetric, capacity sharing may intensify equilibrium competition and hurt firm profitability through reversing the firms’ relative pricing aggressiveness. The supplementary appendix is available at https://doi.org/10.1287/mnsc.2017.2796 . This paper was accepted by Eric Anderson, marketing.